PERLAWANAN DALAM EKSEKUSI OBYEK JAMINAN HAK TANGGUNGAN BERDASARKAN TITEL EKSEKUTORIAL - RM Anton Suyatno (Jurnal Hukum dan Peradilan, 2014)
Loan resolution through the execution of a security interest by title guarantee executorial implemented by involving the courts. The process of settlement is done by banks as creditors without filing a lawsuit first. Banking immediately submit the petition to the Chairman of the local District Court. In the petition Execution Mortgage, the petitioner (creditors) must attach the documents as a condition of submission of application execution. The execution of the object Mortgage guarantee in practice often fought on the basis of unclear legal status object ownership guarantees, or the amount of debt that is uncertain (fix). In some cases it was found that the resolution of bad loans through the execution of the object of the guarantee Encumbrance by title executorial obstacles and takes a long time. In Decision No. 383/Pdt.G/2008/PN.Jkt.Bar. found that it takes approximately four (4) years (October 1, 2007 to 10 November 2011) for the creditor to execute a guarantee Encumbrance. This fact is certainly not in line with the objectives of UUHT, one of which states that the execution Encumbrance implemented easily and surely. Keyword: Resistance, Execution, Encumbrance